2015
DOI: 10.1515/nuka-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resonant second harmonic generation in plasma based on density transition

Abstract: Abstract. Resonant second harmonic generation of a relativistic self-focusing laser in plasma with density ramp profi le has been investigated. A high intense Gaussian laser beam generates resonant second harmonic beam in plasma with density ramp profi le. The second harmonic undergoes periodic focusing in the plasma channel created by the fundamental wave. The normalized second harmonic amplitude varies periodically with distance and attains maximum value in the focal region. Enhancement in the second harmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The self-focusing benefits for right-handed polarisation and the benefits of defocusing for left-handed polarisation are also increased by a decrease in plasma temperature and an increase in the oblique magnetic field [19]. Wani et al [20] reported that semiconductor quantum plasma (SCQP) had enhanced the accuracy of self-focusing. The Hermite cosh gaussian (HchG) beam grants freedom to the decentred parameter, significantly altering the laser beam's ability to focus on its own quip.…”
Section: Introductionmentioning
confidence: 99%
“…The self-focusing benefits for right-handed polarisation and the benefits of defocusing for left-handed polarisation are also increased by a decrease in plasma temperature and an increase in the oblique magnetic field [19]. Wani et al [20] reported that semiconductor quantum plasma (SCQP) had enhanced the accuracy of self-focusing. The Hermite cosh gaussian (HchG) beam grants freedom to the decentred parameter, significantly altering the laser beam's ability to focus on its own quip.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al studied the self-focusing of an elliptic-Gaussian laser beam in relativistic ponderomotive plasma using a density ramp profile [15]. Kant and Thakur investigated the enhanced resonant second harmonic generation of a relativistically self-focused laser beam in plasma with density transition (ramp) [16].…”
Section: Introductionmentioning
confidence: 99%